COMPILATION OF THE YEAR AND AGE OF KOMIL KHOREZMI IN THE MANUSCRIPTION COPIES OF “TAZKIRAI SHUARO” - do’stova, surayyo (FILOLOGIYA UFQLARI JURNALI, 2023)
COMPILATION OF THE YEAR AND AGE OF KOMIL KHOREZMI IN THE MANUSCRIPTION COPIES OF “TAZKIRAI SHUARO”